VIRTUAL REALITY: A SOCIOCULTURAL DIMENSION - Skyba, Oksana (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
The article examines the transformation of the sociocultural space under the influence of virtual reality as an artificially constructed environment of human activity. It is shown that virtual reality is no longer merely a technological tool but acquires the status of a specific sociocultural space in which new forms of interaction, communication, and experience construction emerge. The aim and tasks. The aim of the study is to provide a socio-philosophical analysis of the integration of virtual reality into the contemporary sociocultural space and to clarify the role of immersive technologies in transforming human interaction with artificially constructed environments. The tasks include analyzing the evolution of the concept of virtual reality, identifying the features of its integration into sociocultural space, characterizing the role of immersive technologies, and determining the sociocultural consequences of virtualization. Research methods. The methodological framework combines the method of the unity of historical and logical analysis, as well as systemic and dialectical approaches. These methods enable the study of virtual reality as a dynamic phenomenon and reveal the contradictory nature of its integration into social life. Research results. It is established that the idea of an alternative reality evolves from classical philosophical interpretations of ideal or transcendent being to the modern understanding of virtual reality as a technologically mediated environment. Particular attention is paid to immersive technologies, which ensure different degrees of human involvement in virtual environments and significantly influence patterns of interaction, communication, and perception. Discussion. The analysis demonstrates that virtual reality functions as a component of contemporary culture and develops through complex interactions between technological infrastructure, communication practices, and individual characteristics of users. Immersive technologies play a significant role in shaping the depth and quality of engagement with virtual environments. Conclusions. The integration of virtual reality into the sociocultural space is a nonlinear process determined by both technological conditions and human factors. Immersive technologies mediate the transition from superficial interaction to deeper involvement, thereby contributing to transformations in communication, social practices, and value orientations.